PENGARUH BERBAGAI KONSENTRASI LARUTAN KAPORIT (CaHOCl) UNTUK DIPPING PUTING SUSU KAMBING PERAH TERHADAP TOTAL BAKTERI DAN pH SUSU - Sasongko, Deddy Ari; Suprayogi, Teguh Hari; Suyuthi, Suranto Moch (Animal Agriculture Journal, 2012)
This study aimed to determine the effect of various concentrations of Calcium Hypochloride (CaHOCl) for dairy goat’s teat dipping towards total of bacteria and milk pH. This research was conducted at the Livestock and Forage Breeding Unit Feed Malang on 23 July to 23 August 2011. The materials used in this study were 12 dairy goats (PE) lactation. Materials used disinfectant is Calcium Hypochloride (CaHOCl) Tjiwi artificial chemicals. Equipment used plate count agar, measuring cups, syringes, glass dyer for dipping, a capacity of 250 ml sample bottles were glass, stop watch, and a light-proof thermos brand Hanna pH meter with a scale of 0-14 with a sensitivity of 0.01. Treatment applied is T0 (without dipping), T1 (dipping with concentration of Calcium Hypochloride (CaHOCl) 0.1%) and T2 (dipping with concentration of Calcium Hypochloride (CaHOCl) 0.2%). Parameters observed in this study are the total of bacteria and milk pH. The design used was completely randomized design (CRD) with 3 treatments and 4 replications. The data obtained were then analyzed using ANOVA. The results showed that different concentrations of disinfectants used for dipping teats of dairy goat milk showed the difference of total bacteria and pH of milk. Mean total bacterial T0, T1 and T2 respectively is 15,1 x 106 CFU/ml; 6,98 x 105 CFU/ml and 3,46 x 105 CFU/ml. Mean pH of milk T0, T1 and T2 respectively is 6.47; 6.53 and 6.54. Based on this research can be concluded that dipping the nipple of dairy goats using Calcium Hypochloride (CaHOCl) with the low concentration (0.1%) have been able to reduce the number of bacteria and maintain the pH of milk.Keywords: dipping, total of bacteria, milk pHABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh berbagai konsentrasi desinfektan untuk dipping putting susu kambing perah terhadap total bakteri dan pH susu. Penelitian ini dilaksanakan di UPT Pembibitan Ternak dan Hijauan Makanan Ternak Malang pada tanggal 30 Juli – 5 Agustus 2011. Materi yang digunakan dalam penelitian ini adalah 12 ekor kambing perah (PE) laktasi. Bahan desinfektan yang digunakan adalah kaporit (CaHOCl) buatan Tjiwi kimia. Peralatan yang digunakan plate count agar, gelas ukur, spuit, gelas pencelup untuk dipping, botol sampel kapasitas 250 ml yang terbuat dari kaca, stop watch, termos kedap cahaya dan pH meter merek Hanna dengan skala 0 – 14 dengan kepekaan 0,01. Perlakuan yang diterapkan adalah T0 (Tanpa Dipping), T1 (Dipping dengan konsentrasi larutan kaporit (CaHOCl) 0,1% ) dan T2 (Dipping dengan konsentrasi larutan kaporit (CaHOCl) 0,2%). Parameter yang diamati dalam penelitian ini adalah total bakteri dan pH susu. Rancangan yang digunakan adalah Rancangan Acak Lengkap (RAL) dengan 3 perlakuan dan 4 ulangan. Data yang diperoleh kemudian dianalisis menggunakan Anova. Hasil penelitian menunjukkan bahwa berbagai konsentrasi desinfektan yang digunakan untuk dipping putting susu kambing perah menunjukkan perbedaan terhadap total bakteri dan pH susu. Rataan total bakteri T0, T1 dan T2 masing-masing yaitu 3,51 x 106 CFU/ml; 5,16 x 105 CFU/ml dan 4,35 x 105 CFU/ml. Rataan pH susu T0, T1 dan T2 masing-masing adalah 6,47; 6,53 dan 6,54.Kata kunci: dipping, total bakteri, pH susu